Aggregation‐Induced Emission and Sensing Characteristics of Triarylborane–Oligothiophene–Dicyanovinyl Triads. Issue 48 (28th September 2016) - Kumar, George Rajendra; Sarkar, Samir Kumar; Thilagar, Pakkirisamy
Abstract: The design, synthesis and aggregation‐induced emission properties of a new series of triarylborane–oligothiophene–dicyanovinyl (DCV) conjugates4 –6 (A–D–A' type molecular configuration) are reported. The optical properties of4 –6 can be modulated by judiciously varying the number of thiophene units between electron deficient boryl and dicyanovinyl units. Compound6 with terthiophene spacer showed highly red‐shifted absorption and emission compared to5 and4 with bithiophene and monothiophene spacers, respectively. Compounds5 and6 show aggregation‐induced emission enhancement in water/THF mixtures. Compounds5 and6 also showed solvent viscosity dependent emission characteristics. All the three compounds show distinct optical responses for small anions such as fluoride and cyanide. Filter paper strips coated with compounds5 and6 can detect F − and CN − in aqueous media with different colorimetric responses. Abstract : Hazard detectors : The design and synthesis of a series of triarylborane–oligothiophene–dicyanovinyl triads4 –6 (A–D–A') is reported (see figure). The optical properties of4 –6 were elegantly modulated by judiciously varying the number of thiophenyl spacers between the acceptors. Compounds5 and6 are AIE active and also exhibit significant luminescence in a PMMA matrix. Filter paper strips coated with compounds5 and6 can detect F − and CN − in aqueous media with different colorimetric responses.